Carbon based thermoelectric materials for energy harvesting - Qiu, Zhe (2015)
A typical carbon nanotube has a good electrical conductivity, abundant availability, and great flexibility that are best suited to the electrical devices, but its extreme low Seebeck coefficient and high thermal conductivity have prevented it from being a feasible candidate for thermoelectric devices. In this report, a new approach to enhance carbon nanotubes based composites has been presented. It has the advantages of easy-to-manufacture, lightweight, versatility, and less toxicity compared to traditional inorganic thermoelectric materials. Hybrid nanocomposites consist of single walled carbon nanotubes (SWCNTs) and silver telluride (Ag2Te) nanoparticles synthesized by solvothermal technique. This technique used carbon nanotubes (CNTs) as template and silver precursors reacting with TOP–Te. XRD and TEM images show that Ag2Te nanoparticles were randomly embedded on CNTs bundles. The CNTs/Ag2Te nanocomposites exhibit a higher electrical conductivity > 20 000 S/m and an enhanced Seebeck coefficient up to 228 μV K−1 with a negative sign (n-type), which is more than one order of magnitude higher than all the reported CNTs-based materials’ values previously. This study has confirmed the synergistic enhancement effects within CNTs/Ag2Te composites. It also suggests that similar approach of constructing composites structure by using other materials with high thermoelectric properties would be a novel and effective strategy to improve the thermoelectric performances of CNTs-based materials. All in all, CNTs-based composites materials show a promising potential to be utilized in next-generation thermoelectric devices.